Enabling pathways to opportunity through a skills‐based architecture. Issue 1 (22nd March 2021) - DeMark, Sarah; Kozyrev, Joann
Abstract: Individuals need the shortest path to opportunity and employers require the shortest path to a skilled diverse workforce. To solve for this, Western Governors University (WGU) has created a skills‐based architecture to map our competencies and credentials to high‐demand knowledge, and technical skills as well as powerful, enduring, employability skills like critical thinking, social‐emotional intelligence, creativity, and the ability to work with diverse collaborators. At WGU, these high‐demand industry‐relevant skills are mapped into educational experiences and credentials to better support the upskilling and reskilling needs required for our dramatically altered job market. WGU also intends to surface these skills and competency achievements to employers, thereby facilitating a more efficient and effective match of talent to opportunity. This skills‐based architecture enables WGU to create new in‐demand program offerings, better supporting underserved populations through new pathways and onramps to education while the alignment to skills ensures pathways to careers and a strong return on investment for students.